2004
DOI: 10.1159/000076030
|View full text |Cite
|
Sign up to set email alerts
|

The Central Serotonergic System Mediates the Analgesic Effect of Electroacupuncture on <i>Zusanli</i> (ST36) Acupoints

Abstract: Evidence in the past decade indicates that the mechanisms of anti-nociception of electroacupuncture (EAc) involve actions of neuropeptides (i.e., enkephalin and endorphin) and monoamines (i.e., serotonin and norepinephrine) in the central nervous system. Our present results using a subcutaneous injection of formalin to test pain sensation in mice provide further understanding of the involvement of serotonin in the actions of EAc-induced analgesia. Our observations show that (1) EAc at three different frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…The acupoints of DU20 and ST36 can rescue the imbalance of the 5-HT receptor, which is one of the major molecular causes of depression. [20][21] This finding provides a reliable basis for the treatment of depression. Interestingly, we observed a good curative effect in the acupuncture control group.…”
Section: Discussionmentioning
confidence: 88%
“…The acupoints of DU20 and ST36 can rescue the imbalance of the 5-HT receptor, which is one of the major molecular causes of depression. [20][21] This finding provides a reliable basis for the treatment of depression. Interestingly, we observed a good curative effect in the acupuncture control group.…”
Section: Discussionmentioning
confidence: 88%
“…The hypothesis for this improvement is based on the supposition that the release of substances in the CNS, mainly 5-HT, [13][14][15] as a result of acupuncture, could have decreased symptoms because 5-HT dysfunction occurs in PMDD. 4 9 This present investigation is methodologically different from the previous study as it was a randomised clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…It is now viewed as an alternative method of medicine in Western countries [7,27]. Electroacupuncture (EA) is a modified acupuncture technique that, as its name implies, utilizes electrical stimulation, and its analgesic effects on different types of acute pains and persistent inflammatory pains have been shown in rodents and humans [2,4,20,28,35,49]. In the last 2 decades, several clinical studies have also reported the beneficial effects of acupuncture or EA on neuropathic pain [1,14,46].…”
Section: Introductionmentioning
confidence: 99%